CONDITIONS AND FACTORS OF THE CAPTURE OF BUKHARA AUTHORITY BY ABDULLAH KHAN (Conferencea, 2024)
The article describes the processes of the occupation of Bukhara by Abdullah Khan, a statesman who was politically divided in Movaounnahr in the 16th century, and flourished in this division. Also, the information given in the sources is compared, and Abdullah Khan's opportunities to enter the political arena are highlighted.